Wheat Growth Parameters in Response to Irrigation Salinity in Wheat—Triticum aestivum L. - Brajesh Kumar; Naresh Kumar Arora; Raman Kumar; Sonu Sharma; Monu Sharma (Biology and Life Sciences Forum, 2023)
Crops grown on salt-affected soils may experience physiological drought stress, ion toxicity, and mineral shortage, resulting in lower growth and output. Salinity is the most important abiotic factor limiting crop development and output globally. Improving agri-food production in salt-prone locations is critical for meeting rising food demands in the near future. A pot experiment was conducted to study the impact of saline irrigation water on the chemical properties of sandy loam soil and their influence on growth, yield, and other biometric parameters of wheat (Triticum aestivum L.), Cv KRL 213 in the farmer’s field at Karnal. Three irrigation water treatments, i.e., Tube well water (TW), saline water (SW1, ECiw 10.0 dS m−1, SAR 5.0 mmol1/2 L−1/2), and concentrated saline water (SW2, ECiw 10.0 dS m−1, SAR 5.0 mmol1/2L−1/2), were applied in reclaimed normal soil (pHs 7.5 and ECe 1.0 dS m−1). The results showed that, when low-quality water was applied to normal soil, salt increased, increasing the likelihood of normal soil deterioration. Continuous irrigation with concentrated salt water (SW2) raised the ECe of the root zone soil, which had a negative impact on wheat crop mortality (approximately 70%). In post-wheat samples, soil organic carbon, calcium carbonate, and cation exchange capacity (CEC) remained constant across all water treatments. Concentrated salty water (SW2) is not advised on its own, but it can be used in conjunction with other management practices (by mixing with rain, pond, or canal water) to reduce the negative impacts on soil chemical characteristics and crop development.